2004
DOI: 10.1007/s00330-004-2403-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of image quality of multislice spiral CT scans of the head and neck region using a raw data-based multidimensional adaptive filtering (MAF) technique

Abstract: The purpose was to evaluate the potential of the multidimensional adaptive filtering (MAF) technique by investigating its effects on image noise and image quality in multislice spiral CT (MSCT) examinations of the head and neck region. Fifty patients with head and neck tumors were examined using MSCT with a high resolution protocol. Reconstructions were performed using dedicated reconstruction software with a standard algorithm both without and with MAF using different modification. In all reconstructions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Recent studies have demonstrated the value of noise reduction filters in images acquired with reduced tube current [5][6][7]. Whilst effectively smoothing, most of these noise-reduction filters cause a perceptible loss of anatomic structure delineation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the value of noise reduction filters in images acquired with reduced tube current [5][6][7]. Whilst effectively smoothing, most of these noise-reduction filters cause a perceptible loss of anatomic structure delineation.…”
Section: Introductionmentioning
confidence: 99%
“…However, anatomical distortions, scarring and granulation after surgery and/or radiotherapy compromise the ability of clinical examination and morphological imaging [ultrasound, computed tomography (CT), magnetic resonance imaging (MRI)] to detect a recurrent/persistent tumour [2][3][4][5][6]. Therefore, metabolic imaging modalities, such as positron emission tomography (PET) or single photon emission tomography (SPECT) have been proposed as an alternative technique for this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging investigations for diagnosis of significant carotid artery stenosis include digital subtraction angiography (DSA), MR angiography (MRA), Doppler ultrasonography (US) and also multi-detector row CT angiography (CTA) [6][7][8][9][10][11][12][13][14][15][16]. DSA is still considered the gold standard for evaluation of carotid artery stenosis, but the risk of neurological complications is estimated to be between 0.05 to 0.5% [17,18].…”
Section: Introductionmentioning
confidence: 99%